Analisis Metode dan Konten Dakwah yang Diminati pada Remaja - Muhamad Parhan; Yuni Rahmawati; Imelda Rara Rahmawati; Hasna Aisyah Rastiadi; Maysaroh Maysaroh (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2022)
Since the pandemic, da'wah has begun to develop by involving technology such as using zoom, youtube, Instagram, and so on. In addition to the da'wah method, the content of da'wah is also essential and must be considered because of da'wah material influences teenagers' interest in listening to da'wah. The purpose of this research is to analyze the methods and content of da'wah that are suitable for teenagers, the method used is quantitative in the form of a survey of teenagers. Based on the information obtained through a study of teenagers, around 86.3% of teenagers still like to listen to da'wah during this pandemic. Still, only 38.4% of teenagers who often listen to da'wah and 61.6% rarely listen to da'wah. Around 72.6% of teenagers during the pandemic prefer to listen to da'wah through YouTube media with da'wah content about life, and 71.2% of teenagers prefer the da'wah method in the form of examples and examples. This shows that technological advances and youth synergize well so that da'wah content is packaged more attractively, and effectively and reaches wider attention.